Comparative Transcriptomic Approaches Exploring Contamination Stress Tolerance in Salix sp. Reveal the Importance for a Metaorganismal de Novo Assembly Approach for Nonmodel Plants . Issue 1 (2nd May 2016) - Brereton, Nicholas J. B.; Gonzalez, Emmanuel; Marleau, Julie; Nissim, Werther Guidi; Labrecque, Michel; Joly, Simon; Pitre, Frederic E.
Abstract : Shared metatranscriptomic responses to petroleum hydrocarbon contamination in ten cultivars of field-grown willow expose native and foreign organism gene expression of effective phytoremediation. Abstract: Metatranscriptomic study of nonmodel organisms requires strategies that retain the highly resolved genetic information generated from model organisms while allowing for identification of the unexpected. A real-world biological application of phytoremediation, the field growth of 10 Salix cultivars on polluted soils, was used as an exemplar nonmodel and multifaceted crop response well-disposed to the study of gene expression. Sequence reads were assembled de novo to create 10 independent transcriptomes, a global transcriptome, and were mapped against the Salix purpurea 94006 reference genome. Annotation of assembled contigs was performed without a priori assumption of the originating organism. Global transcriptome construction from 3.03 billion paired-end reads revealed 606, 880 unique contigs annotated from 1588 species, often common in all 10 cultivars. Comparisons between transcriptomic and metatranscriptomic methodologies provide clear evidence that nonnative RNA can mistakenly map to reference genomes, especially to conserved regions of common housekeeping genes, such as actin, α/β-tubulin, and elongation factor 1-α. In Salix, Rubisco activase transcripts were down-regulated in contaminated trees across all 10 cultivars, whereas thiamine thizole synthase and CP12, a Calvin Cycle master regulator, were uniformly up-regulated. De novo assembly approaches, with unconstrained annotation, can improve data quality; care should be taken when exploring such plant genetics to reduce de facto data exclusion by mapping to a single reference genome alone. Salix gene expression patterns strongly suggest cultivar-wide alteration of specific photosynthetic apparatus and protection of the antenna complexes from oxidation damage in contaminated trees, providing an insight into common stress tolerance strategies in a real-world phytoremediation system.